Nanoporous graphene enriched with Fe/Co-N active sites as a promising oxygen reduction electrocatalyst for anion exchange membrane fuel cells - Palaniselvam, Thangavelu; Kashyap, Varchaswal; Bhange, Siddeswar N.; Baek, Jong-Beom; Kurungot, Sreekumar (Advanced Functional Materials, 2016)
Here, a simple but efficient way is demonstrated for the preparation of nanoporous graphene enriched with Fe/Co-nitrogen-doped active sites (Fe/Co-NpGr) as a potential electrocatalyst for the electrochemical oxygen reduction reaction (ORR) applications. Once graphene is converted into porous graphene (pGr) by a controlled oxidative etching process, pGr can be converted into a potential electrocatalyst for ORR by utilizing the created edge sites of pGr for doping nitrogen and subsequently to utilize the doped nitrogens to build Fe/Co coordinated centers (Fe/Co-NpGr). The structural information elucidated using both XPS and TOF-SIMS study indicates the presence of coordination of the M-N (M = Fe and Co)-doped carbon active sites. Creation of this bimetallic coordination assisted by the nitrogen locked at the pore openings is found to be helping the system to substantially reduce the overpotential for ORR. A 30 mV difference in the overpotential () with respect to the standard Pt/C catalyst and high retention in half wave potential after 10 000 cycles in ORR can be attained. A single cell of an anion exchange membrane fuel cell (AEMFC) by using Fe/Co-NpGr as the cathode delivers a maximum power density of approximate to 35 mWcm(-2) compared to 60 mWcm(-2) displayed by the Pt-based system.
Keywords: electrocatalyst; nitrogen doping; oxygen reduction reaction; porous grapheme; quantum dots

Activity tuning of cobalt ferrite nanoparticles anchored on N-doped reduced graphene oxide as a potential oxygen reduction electrocatalyst by Zn substitution in the spinel matrix - Kashyap, Varchaswal; Singh, Santosh K.; Kurungot, Sreekumar (Chemistry Select, 2017)
Development of highly efficient and durable ORR catalysts by using non-platinum group metals (such as Co, Fe, Mn, and Zn) is a challenging task in the forward path towards the realization of low-cost energy devices in the commercial stream. The present work deals with an effective strategy wherein an efficient Pt-free electrocatalyst for oxygen reduction reaction (ORR) is prepared by stoichiometrically substituting some fraction of Fe with Zn in cobalt ferrite and anchoring these spinel nanoparticles on nitrogen doped reduced graphene oxide (N-rGO). Zn substitution is found to be significantly altering the ratio of Fe2+/Fe3+ in the cobalt ferrite nanocrystal system with a concomitant promotional influence on its electrocatalytic activity towards ORR. The nanoparticle composition with a Co, Fe and Zn molar ratio of 1.0:1.7:0.3, represented by the formula CoFe1.7Zn0.3O4(CFZn(0.3)), supported over N-rGO has shown 10 mV and 20 mV positive shift in the onset and half-wave potentials, respectively, for ORR in 0.1 M KOH in comparison to the nanoparticles of CoFe2O4 supported over N-rGO (CF/N-rGO). The optimum Zn substitution is found to be narrowing down the difference with the state-of-the-art Pt/C for ORR by 100 and 110 mV in terms of the onset and half-wave potentials, respectively. Most significantly, the homemade catalyst is found to be clearly outperforming the Pt catalyst in terms of the limiting current density and electrochemical durability.
Keywords: Carbon Nano-fiber; Cathod Catalyst; CoFe2O4; Evolution; Magnetic-properties; Membrane fuel- Cell; Metal-Air Batteries; N-doped graphene; Nanocrystalline; nanocrystals; oxygen reduction reaction; performance; Platinium; solvothermal synthesis; Zn substituted cobalt ferrite

Efficient and durable oxygen reduction electrocatalyst based on CoMn alloy oxide nanoparticles supported over N-doped porous graphene - Singh, Santosh K.; Kashyap, Varchaswal; Manna, Narugopal; Bhange, Siddheshwar N.; Soni, Roby; Boukherroub, Rabah; Szunerits, Sabine; Kurungot, Sreekurnar (ACS Catalysis, 2017)
Transition metal oxide derived materials are very important for various applications, such as electronics, magnetism, catalysis, electrochemical energy conversion, and storage. Development of efficient and durable catalysts for the oxygen reduction reaction (ORR), an important reaction in fuel cells and metal air batteries, is highly desirable. Moreover, the futuristic catalysts for these applications need to be costeffective in order to ensure a competitive edge for these devices in the energy market. This article describes the synthesis of a cost-effective and efficient electrocatalyst for ORR It is based on supporting CoMn alloy oxide nano particles on N-doped porous graphene through a simple and scalable microwave irradiation method. Microwave irradiation was found to be very crucial for the fast creation of pores in the graphene framework with a concomitant formation of the CoMn alloy oxide nanoparticles. A series of catalysts have been synthesized by varying the Co:Mn ratio, among which, the one with the Co:Mn ratio of 2:1 [designated as CoMn/pNGr(2:1)] displayed remarkably higher ORR activity in 0.1 M KOH solution. It showed a similar to 60 mV potential shift with a low Tafel slope of 74 mV/decade, which is comparable to that derived from the commercial Pt/C catalyst. This high activity of CoMn/pNGr(2:1) has been credited to the cooperative effect arising from the metal entities and the defects present in the N-doped porous graphene. Finally, real system-level validations of the use of CoMn/pNGr(2:1) as cathode catalyst could be performed by fabricating and testing single-cells of an anion-exchange membrane fuel cell (AEMFC) and a primary Zn-air battery, which successfully demonstrated the efficiency of the catalyst to facilitate ORR in real integrated systems of the single-cell assemblies.
Keywords: anion-exchange membrane fuel cell; cooperativity effect; microwave synthesis; oxygen reduction reaction; porous N-doped graphene; Zn-air battery

Iron Catalyzed Hydroformylation of Alkenes under Mild Conditions: Evidence of an Fe(II) Catalyzed Process - Pandey, Swechchha; Raj, K. Vipin; Shinde, Dinesh R.; Vanka, Kumar; Kashyap, Varchaswal; Kurungot, Sreekumar; Vinod, C. P.; Chikkali, Samir H. (Journal of the American Chemical Society, 2018)
Earth abundant, first row transition metals offer a cheap and sustainable alternative to the rare and precious metals. However, utilization of first row metals in catalysis requires harsh reaction conditions, suffers from limited activity, and fails to tolerate functional groups. Reported here is a highly efficient iron catalyzed hydroformylation of alkenes under mild conditions. This protocol operates at 10-30 bar syngas pressure below 100 degrees C, utilizes readily available ligands, and applies to an array of olefins. Thus, the iron precursor [HFe(CO)(4)](-)[Ph3PNPPh3](+) (1) in the presence of triphenyl phosphine catalyzes the hydroformylation of 1-hexene (S2), 1-octene (S1), 1-decene (S3), 1-dodecene (S4), 1-octadecene (S5), trimethoxy(vinyl)silane (S6), trimethyl(vinyl)silane (S7), cardanol (S8), 2,3-dihydrofuran (S9), allyl malonic acid (S10), styrene (S11), 4-methylstyrene (S12), 4-iBu-styrene (S13), 4-tBu-styrene (S14), 4-methoxy styrene (S15), 4-acetoxy styrene (S16), 4-bromo styrene (S17), 4-chloro styrene (S18), 4-vinylbenzonitrile (S19), 4-vinylbenzoic acid (S20), and allyl benzene (S21) to corresponding aldehydes in good to excellent yields. Both electron donating and electron withdrawing substituents could be tolerated and excellent conversions were obtained for S11-S20. Remarkably, the addition of 1 mol % acetic acid promotes the reaction to completion within 16-24 h. Detailed mechanistic investigations revealed in situ formation of an iron-dihydride complex [H2Fe(CO)(2)(PPh3)(2)] (A) as an active catalytic species. This finding was further supported by cyclic voltammetry investigations and intermediacy of an Fe(0)-Fe(II) species was established. Combined experimental and computational investigations support the existence of an iron-dihydride as the catalyst resting state, which then follows a Fe(II) based catalytic cycle to produce aldehyde.

Realizing high capacitance and rate capability in polyaniline by enhancing the electrochemical surface area through induction of superhydrophilicity - Soni, Roby; Kashyap, Varchaswal; Nagaraju, Divya; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2018)
Polyaniline (PANI) as a pseudocapacitive material has very high theoretical capacitance of 2000 F g(-1). However, its practical capacitance has been limited by low electrochemical surface area (ESA) and unfavorable wettability toward aqueous electrolytes. This work deals with a strategy wherein the high ESA of PANI has been achieved by the induction of superhydrophilicity together with the alignment of PANI exclusively on the surface of carbon fibers as a thin layer to form a hybrid assembly. Superhydrophilicity is induced by electrochemical functionalization of the Toray carbon paper, which further induces superhydrophilicity to the electrodeposited PANI layer on the paper, thereby ensuring a high electrode-electrolyte interface. The Toray paper is electrochemically functionalized by the anodization method, which generates a highly active electrochemical surface as well as greater wettability (superhydrophilic) of the carbon fibers. Because of the strong interaction of anilinium chloride with the hydrophilic carbon surface, PANI is polymerized exclusively over the surface of the fibers without any appreciable aggregation or agglomeration of the polymer. The PANI-Toray paper assembly in the solid-state prototype supercapacitor can provide a high gravimetric capacitance of 1335 F g(-1) as well as a high areal capacitance of 1.3 F cm(-2) at a current density of 10 A g(-1). The device also exhibits high rate capability, delivering 1217 F g(-1) at a current density of 50 A g(-1) and a high energy density of 30 W h kg(-1) at a power density of 2 kW kg(-1).
Keywords: electrochemical active sulfate area; electrochemical functionalization; electropolymerization; polyaniline; supercapacitor; superhydrophilic

Zirconium-substituted cobalt ferrite nanoparticle supported n-doped reduced graphene oxide as an efficient bifunctional electrocatalyst for rechargeable Zn-air battery - Kashyap, Varchaswal; Kurungot, Sreekumar (ACS Catalysis, 2018)
Solvothermal synthesis of zirconium-substituted cobalt ferrite nanoparticles was accomplished by the introduction of zirconium (Zr) in the spinel matrix to obtain a cost-effective and robust electrocatalyst that does not use noble metals. A variation in the cobalt ferrite structure CoFe2−xZrxO4 with Zr (0.1−0.4) substitution has significantly altered the overpotential for the electrocatalytic oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), leading to an optimum composition of CFZr(0.3). The incorporation of the foreign Zr4+ ion in the cobalt ferrite spinel lattices has effectively enhanced the oxygen evolution reaction (OER) activity in comparison to the parent cobalt ferrite (CF) nanocrystals. However, a nominal change in the ORR current density has been observed due to Zr incorporation. For the OER, the Zr-substituted catalyst has shown a 40 mV negative shift in the overpotential in comparison with the CF nanoparticles at 10 mA/cm2 current density. Interestingly, the in situ grafting of Zr-substituted cobalt ferrite nanoparticles over N-doped reduced graphene oxide (CFZr(0.3)/N-rGO) results in remarkably enhanced performance during the ORR and moderately favored the OER with an overall potential difference (ΔE) of 0.840 V. The enhanced bifunctional electrocatalytic activity of the material is crucial for the fabrication of high-performance rechargeable Zn−air batteries (ZABs). The prepared catalyst exhibited an overpotential of 80 mV for the ORR in comparison with the state-of-the-art (Pt/C) catalyst and an overpotential of 340 mV at 10 mA/cm2 current density for the OER from the standard value (1.23 V vs RHE). This potential bifunctional electrocatalyst has been employed as an electrode material for the fabrication of a primary ZAB, where it exhibited discharge capacities of 727 and 730 mAh/g at current densities of 20 and 30 mA/cm2 , respectively, under ambient conditions. The notable performance of the catalyst as a bifunctional material is observed during the cycling of the rechargeable ZAB. The prepared catalyst showed an increase of 200 mV in the overall operating overpotential after cycling for 10 cycles at 15 mA/cm2 in comparison to the 350 mV increase shown by the Pt/C catalyst.
Keywords: N-doped reduced graphene oxide; Oxygen Evolution Reaction; oxygen reduction reaction; zirconium-substituted cobalt ferrite

High-performing PGM-free AEMFC cathodes from carbon-supported cobalt ferrite nanoparticles - Peng, Xiong; Kashyap, Varchaswal; Ng, Benjamin; Kurungot, Sreekumar; Wang, Lianqin; Varcoe, John R.; Mustain, William E. (Catalysts, 2019)
Efficient and durable non-precious metal electrocatalysts for the oxygen reduction reaction (ORR) are highly desirable for several electrochemical devices, including anion exchange membrane fuel cells (AEMFCs). Here, cobalt ferrite (CF) nanoparticles supported on Vulcan XC-72 carbon (CF-VC) were created through a facile, scalable solvothermal method. The nano-sized CF particles were spherical with a narrow particle size distribution. The CF-VC catalyst showed good ORR activity, possessing a half-wave potential of 0.71 V. Although the intrinsic activity of the CF-VC catalyst was not as high as some other platinum group metal (PGM)-free catalysts in the literature, where this catalyst really shined was in operating AEMFCs. When used as the cathode in a single cell 5 cm(-2) AEMFC, the CF-VC containing electrode was able to achieve a peak power density of 1350 mW cm(-2) (iR-corrected: 1660 mW cm(-2)) and a mass transport limited current density of more than 4 A cm(-2) operating on H-2/O-2. Operating on H-2/Air (CO2-free), the same cathode was able to achieve a peak power density of 670 mW cm(-2) (iR-corrected: 730 mW cm(-2)) and a mass transport limited current density of more than 2 A cm(-2). These peak power and achievable current densities are among the highest reported values in the literature to date.
Keywords: AEMFC; cobalt; Ferrite; high-performing; non-PGM; vulcan

In-situ generated Mn3O4-reduced graphene oxide nanocomposite for oxygen reduction reaction and isolated reduced graphene oxide for supercapacitor applications - Jha, Plawan Kumar; Kashyap, Varchaswal; Gupta, Kriti; Kumar, Vikash; Debnath, Anil Krishna; Roy, Debashree; Rana, Shammi; Kurungot, Sreekumar; Ballav, Nirmalya (Carbon, 2019)
We have generated in situ nanocomposite of Mn3O4 and reduced graphene oxide (rGO) upon employing wet-chemical reduction of graphene oxide (GO) by Mn(II) salt as mild-reducing agent for the first time and examined the oxygen reduction reaction (ORR) activity in 0.1 M KOH electrolyte. The half-wave potential (E-1/2) of the nanocomposite catalyst (20% Mn3O4-rGO/C) was found to be around -0.153 V which is only similar to 87 mV negative from the commercially available catalyst (20% Pt/C). Remarkably, after 5000 linear sweep voltammetry cycles the E-1/2 shifted marginally by 20 mV; and the number of electrons transferred during ORR was estimated to be close to 4. Such an efficient electrocatalytic performance of the nanocomposite was primarily attributed to the synergistic interaction between Mn3O4 and rGO. The fabricated all-solid-state supercapacitor of rGO (extracted from the nanocomposite) in aqueous polyvinyl alcohol-sulfuric acid (PVA-H2SO4) gel polymer electrolyte (GPE) showed C-s value of similar to 310 F/g at a current density of 1 A/g along with long durability (10,000 charge-discharge cycles). All-solid-state flexible rGO supercapacitor exhibited high-flexibility and excellent durability (30,000 cycles with 100% retention of C-s). Our results provide an enormous opportunity in designing transition metal oxides decorated semiconducting reduced graphene oxide nanocomposite platforms for various electrochemical applications. (C) 2019 Elsevier Ltd. All rights reserved.

Medium modulated oxygen reduction activity of Fe/Co active centre-engrafted electrocatalysts - Kashyap, Varchaswal; Anand, Aljo; Soni, Roby; Sreekumar, Kurungot (ChemElectroChem, 2019)
Iron and cobalt metal atoms are effective active centers for the synthesis of carbon-based noble-metal-free catalysts for the oxygen reduction reaction (ORR) owing to their cost-effective intrinsic activity and tunable properties. Annealing of the active center with the conducting carbon enhances the ORR activity significantly. Herein, we have engrafted Fe and Co active centers in the homemade conducting carbon and the ORR performance has been closely observed under acidic and basic pH conditions to understand the influence of the medium and participating moieties towards the performance. In the half-cell reaction, the onset potential and half-wave potential for ORR are governed by the surface intermediates and concomitantly driven by the adsorption energies of the intermediates over the active centers. The iron and cobalt active center-engrafted carbon catalyst behaves differently in acidic and basic electrolytes owing to the dissociation of the surface intermediates. The iron-based catalyst shows improved onset potential against the cobalt-based one. Similarly, the cobalt-based catalyst shows improved half-wave potential against the iron active-center-grafted catalyst. The combined synergistic effect of the two catalysts is realized in the composition represented as Fe/2Co-N-GVC, where improved onset and half-wave potentials are noted in basic medium. A significant variation in the activity of the catalyst is observed as the medium changes from acidic to basic and the effect is directly associated with the surface adsorption of the intermediates.
Keywords: active centers; half-wave potential; Mechanism; oxygen reduction reaction; transition state

[MoS4](2-)-Intercalated NiCo-layered double hydroxide nanospikes: an efficiently synergized material for urine to direct H-2 generation - Nadeema, Ayasha; Kashyap, Varchaswal; Gururaj, Rakshitha; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2019)
Substituting the energy-uphill water oxidation half-cell with readily oxidizable urea-rich urine, a ground-breaking bridge is constructed, combining the energy-efficient hydrogen generation and environmental 6 protection. Hence, designing a robust multifunctional electrocatalyst is desirable for widespread implementation of this waste to fuel technology. In this context, here, we report a simple tuning of the electrocatalytically favorable characteristics of NiCo-layered double hydroxide by introducing [MoS4]2- in its interlayer space. The [MoS4]' insertion as well as its effect on the electronic structure tuning is thoroughly studied via X-ray photoelectron spectroscopy in combination with electrochemical analysis. This insertion induces overall electronic structure tuning of the hydroxide layer in such a way that the designed catalyst exhibited favorable kinetics toward all the required reactions of hydrogen generation. This is why our homemade catalyst, when utilized both as a cathode and anode to fabricate a urea electrolyzer, required a mere X1.37 V cell potential to generate sufficient H2 by reaching the benchmark 10 mA cm-2 in 1 M KOH/0.33 M urea along with long-lasting catalytic efficiency. Other indispensable reason of selecting [MoS4]2- is its high-valent nature making the catalyst highly selective and insensitive to common catalyst-poisoning toxins of urine. This is experimentally supported by performing the real urine electrolysis, where the nanospike-covered Ni foam-based catalyst showed a performance similar to that of synthetic urea, offering its industrial value. Other intuition of selecting [MoS4]2- was to provide a ligand-based mechanism for hydrogen evolution half-cell [hydrogen evolution reaction (HER)] to preclude the HER-competing oxygen reduction. Another crucial point of our work is its potential to avoid the mixing of two explosive product gases, that is, H2 and O-2.
Keywords: hydrogen evolution reaction; Layered double hydroxide; nickel oxyhydroxide; sewage denitrification; urea oxidation reaction; urine/urea electrolysis

Unravelling faradaic electrochemical efficiencies over Fe/Co spinel metal oxides using surface spectroscopy and microscopy techniques - Kashyap, Varchaswal; Pandikassala, Ajmal; Singla, Gourav; Khan, Tuhin Suvra; Haider, M. Ali; Vinod, C. P.; Kurungot, Sreekumar (Nanoscale, 2022)
Cobalt and iron metal-based oxide catalysts play a significant role in energy devices. To unravel some interesting parameters, we have synthesized metal oxides of cobalt and iron (i.e. Fe2O3, Co3O4, Co2FeO4 and CoFe2O4), and measured the effect of the valence band structure, morphology, size and defects in the nanoparticles towards the electrocatalytic hydrogen evolution reaction (HER), the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR). The compositional variations in the cobalt and iron precursors significantly alter the particle size from 60 to <10 nm and simultaneously the shape of the particles (cubic and spherical). The Tauc plot obtained from the solution phase ultraviolet (UV) spectra of the nanoparticles showed band gaps of 2.2, 2.3, 2.5 and 2.8 eV for Fe2O3, Co3O4, Co2FeO4 and CoFe2O4, respectively. Further, the valence band structure and work function analysis using ultraviolet photoelectron spectroscopy (UPS) and core level X-ray photoelectron spectroscopy (XPS) analyses provided better structural insight into metal oxide catalysts. In the Co3O4 system, the valence band structure favors the HER and Fe2O3 favors the OER. The composites Co2FeO4 and CoFe2O4 show a significant change in their core level (O 1s, Co 2p and Fe 2p spectra) and valence band structure. Co3O4 shows an overpotential of 370 mV against 416 mV for Fe2O3 at a current density of 2 mA cm(-2) for the HER. Similarly, Fe2O3 shows an overpotential of 410 mV against the 435 mV for Co3O4 at a current density of 10 mA cm(-2) for the OER. However, for the ORR, Co3O4 shows 70 mV improvement in the half-wave potential against Fe2O3. The composites (Co2FeO4 and CoFe2O4) display better performance compared to their respective parent oxide systems (i.e., Co3O4 and Fe2O3, respectively) in terms of the ORR half-wave potential, which can be attributed to the presence of the oxygen vacancies over the surface in these systems. This was further corroborated in density functional theory (DFT) simulations, wherein the oxygen vacancy formation on the surface of CoFe2O4(001) was calculated to be significantly lower (similar to 50 kJ mol(-1)) compared to Co3O4 (001). The band diagram of the nanoparticles constructed from the various spectroscopic measurements with work function and band gap provides in-depth understanding of the electrocatalytic process.

Fabrication of a 3D iron-modified NiCo2S4 structure on nickel foam as a bifunctional electrocatalyst for overall water splitting - Singla, Gourav; Mahajan, Mani; Bhange, Siddheshwar N.; Kashyap, Varchaswal (New Journal of Chemistry, 2025)
The development of highly efficient bifunctional electrocatalysts that operate effectively in strong electrolytes, with low overpotentials at defined current densities and excellent durability, has become a central focus in research on overall water splitting. In this study, a three-dimensional (3D) sheet-wrapped wire electrocatalyst, composed of Fe-doped NiCo2S4 on nickel foam (NF), was fabricated. This material demonstrated excellent durability for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in an alkaline medium. The uniform distribution of Ni, Co, Fe, and S elements significantly enhanced the electro-catalytic performance. The incorporation of Fe improved activity, with the Fe2.5%-NiCo2S4/NF electrocatalyst achieving overpotentials of 310 mV and 260 mV for the HER and OER, respectively, at a current density of 100 mA cm-2. These results were superior to those of both bare nickel foam and NiCo2S4/NF. The 3D configuration facilitated efficient ion transport and contributed to the remarkable catalytic performance. As a water-splitting electrolyzer in an alkaline electrolyte of 1.0 M KOH, the system delivered a current density of 20 mA cm-2 at a cell voltage of 1.66 V, highlighting the effectiveness of this design strategy.